Encouraging Women’s Economic Opportunities in Croatia : Empirical Evidence of Determinants and Policy Advice - Robayo-Abril, Monica (World Bank, Washington, DC, 2020)
This report analyzes potential factors and determinants affecting female labor force participation in Croatia and identifies potential policy options to facilitate greater participation of women in the labor market. Our results show that the main reason for women’s inactivity in Croatia is child-rearing and other family responsibilities. While Croatia provides a generous maternity leave allowance in comparison with other EU countries, the absence of compulsory paternity leave does not encourage the distribution of child-rearing responsibilities between men and women. Childcare responsibilities also hinder mothers of school-age children from participating in economic activity, although this constraint is lower for mothers of children attending schools with longer school days. Our results also show that both informal and formal factors play a role. Patriarchal views—which were demonstrated to be negatively associated with women’s labor force participation—are more prevalent in Croatia than in many European countries; these views tend to be more prevalent among men, older people, and less-educated individuals. Labor market regulations also play an important role: despite recent reforms aimed at relaxing excessively strict employment protection legislation, introducing more flexibility in the labor market, and boosting active labor market policies, Croatia still lags behind its EU counterparts along these dimensions as is reflected in their low ranking on the ease of hiring and firing, a low proportion of flexible forms of employment, and low expenditure and coverage of active labor market policies. Finally, despite being a common reason in the literature for gender wage gaps, we did not find evidence that the systematic selection of women into low-wage occupations contributes significantly to the observed gender wage gaps.